Building positive Zimbabwean tourism festival, event and destination brand image and equity: a systematic literature review - Farai Chigora; Joram Ndlovu; Brighton Nyagadza (Cogent Social Sciences, 2024)
This article aims to explore the concept of tourism festival and event destination branding and relate it to practices in Zimbabwean festivals and tourism events. The article is therefore based on the following objectives: to understand the concept of tourism festival, event and destination brand image in Zimbabwe; to explain its essence and importance in Zimbabwe; to explore the brand process by mainly looking at market analysis, brand development, brand positioning, brand personality, brand implementation, brand communication and brand tracking; to understand the necessary critical success factors; to explore the constructs of brand equity; and to analyse previous models and discussion in tourism festival and event destination brand equity. A systematic literature review was applied to gather relevant literature related to the study. The process involves a predetermined and comprehensive approach to searching, analysing and synthesising extant literature. Results showed that the image of country’s imagea and vital role in building a positive or negative perception towards a tourism destination image. However, it is essential to note that the image of a country might take a long time to restore itself, even going on for generations. The research study contributes to future research directions by unpacking existing research gaps and advancing knowledge relating to tourism festivals, events and destination brand image in Zimbabwe.